Phase-specific determinants of 100 m freestyle performance in elite swimmers - Qing Gao; Zhanyang He; Gongju Liu; Xun Jin; Houwei Zhu (Scientific Reports)
Abstract The 100 m freestyle is a key event in competitive swimming, where marginal gains across race phases—start, clean swim, turn, and finish—are vital for elite performance. However, sex-specific biomechanical contributions remain underexplored, especially in underwater breakout strategies. This study identifies phase-specific performance determinants, emphasizing sex-stratified correlations and practical insights for optimizing elite-level outcomes. High-speed video analysis and official race data from 59 elite swimmers (29 males and 30 females, including Olympic medalists) were utilized. Spatiotemporal variables and stroke efficiency metrics were collected for each phase. Pearson’s correlation coefficients assessed relationships between race times and phase-specific variables, while repeated measures ANOVA evaluated stability. All clean swim spatiotemporal variables were highly associated with the final race time, especially the first lap (males: r = 0.806, p < 0.001; females: r = 0.850, p < 0.001). A robust start (males: r = 0.501, p = 0.006; females: r = 0.560, p = 0.001) and efficient turn (males: r = 0.588, p = 0.001; females: r = 0.592, p = 0.001) were also crucial, with underwater variables significantly contributing to a faster start and turn. Sex-specific differences in velocity for turn and finish strategies were identified. The study concludes that elite 100 m freestyle performance depends on explosive starts, sustained clean-swimming velocity, and efficient turns, with sex-specific adaptations in pacing and underwater strategy.